(untitled) (Tempo e Argumento, 2022)
This article explores the history of a commonly neglected sector of the population: working children. Specifically, it examines the ways in which the newspaper La Vanguardia - official press organ of the Argentine Socialist Party - dealt and represented, during the first two decades of the 20th century, the problems related to working children from the popular sectors of Buenos Aires. The interest about how the issue of child labor was treated in the written press derives from the centrality that it had at the time studied as a space for the appropriation, formulation and circulation of ideas, that is, in the formation and dissemination of the public opinion.